(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
This paper studies the solutions of variational methods for random ordinary (partial) dierential equations in L2−space. These methods are called Galerkin method, Petrov-Galerkin method, Least-Squares method and Collocation method. Some basic properties of these methods where applying on random problems will be shown throughout some numerical examples. Random models